A simple way to make pre-stressed ceramics with high strength - Yiwang Bao; Fenghua Kuang; Yi Sun; Yueming Li; Detian Wan; Zongyang Shen; Delong Ma; Lingfeng He (Journal of Materiomics, 2019)
A pre-stressing design and a simple fabrication technology to substantially improve the strength of ceramic components are presented. Residual surface compressive stress is generated in ceramic components by pressureless sintering of a green bulk coated with a thin layer of low coefficient of thermal expansion (CTE). The stress level can be controlled by changing the cross-section area ratio, Young's modulus ratio and CTE ratio of the coating. Pre-stressed ZrO2 ceramics coated with Al2O3 can achieve a flexural strength of 1330 ± 52 MPa, 45% higher than their uncoated counterpart. Similarly, the flexural strength of building porcelain tiles is increased by 70%, from 67 ± 3 MPa to 114 ± 5 MPa. The damage tolerance of pre-stressed ZrO2 ceramics is excellent with a high residual strength of ∼1200 MPa in a thermal shock test at 325 °C. This simple technique can improve the mechanical performance of ceramic components with no limitation of size and shape. Keywords: Pre-stressed ceramics, Coating, Strength, Thermal shock resistance